Norcholic Acid Promotes M1 Macrophage Polarization in Acute Pancreatitis by Activating the Wnt/β-Catenin Pathway - Xingyu Liu; Jun Yu; Junning Liu; Qing Zhou; Linfeng Yang; Qian Dai; Jianshui Li; Chuan Lan; Dawei Deng (Frontiers in Bioscience-Landmark)
Background: Acute pancreatitis (AP) is a common gastrointestinal emergency and critical condition worldwide. Given the absence of specific therapeutic targets, managing the progression of AP to severe phases and the accompanying systemic inflammatory response remains challenging. We detected an abnormally elevated expression of norcholic acid (NorCA) in the serum of patients with various types of AP and found that this bile acid is closely associated with the Wnt/β-catenin signaling pathway in the context of AP. This study was designed to investigate NorCA’s dual role as a novel diagnostic biomarker and molecular therapeutic target in AP, with particular emphasis on elucidating its mechanistic regulation of M1 macrophage polarization in RAW 264.7 murine macrophages during AP pathogenesis. Methods: Serum samples from AP patients were collected and screened to identify the levels of NorCA and the extent of metabolic abnormalities using bile acid targeting detection. Transcriptome sequencing and bioinformatics analyses were conducted to investigate the role of the Wnt/β-catenin pathway. To evaluate NorCA’s regulatory effect on M1 macrophage polarization through the Wnt/β-catenin signaling pathway in AP development, we employed flow cytometry, western blotting, and qRT-PCR analyses. Results: NorCA demonstrated a significant elevation in the peripheral blood across different AP subtypes, showing promising diagnostic potential with high sensitivity and specificity. NorCA promotes the polarization of M1 macrophages by activating the Wnt/β-catenin pathway, leading to further inflammation. Treatment with JW74, a specific Wnt/β-catenin inhibitor, significantly reduced the degree of NorCA-induced M1 macrophage polarization. Conclusion: NorCA demonstrates dual clinical utility as both a novel diagnostic biomarker for AP and a promising molecular target for therapeutic intervention in severe AP and its concomitant systemic inflammatory response syndrome (SIRS).